Freedom, Slavery, and Self in Epictetus - Glenn Øystein Wehus (Teologisk Tidsskrift, 2019)
The goal of the philosophy of the Stoic Epictetus, himself a former slave, consisted in attaining freedom. The article explores his notion of freedom, along with the accompanying notion of slavery, and discusses what concept of a human self is brought out in these notions. The real, physical slavery of the Roman Empire is explored as an important backdrop for Epictetus’ metaphorical-philosophical understanding of freedom, and the challenges of Epictetus to the self-understanding of both slaves and free are investigated.